Analisis Faktor-Faktor Dalam Bauran Pemasaran yang Mempengaruhi Keputusan Pembelian Produk (Survei pada Konsumen Coffee Shop Mahalona Kopi Karawang 2023) - Rahmani, Abdullah Imaddudin Hakam; Ramadhan, Fajar (Jurnal Ilmiah Wahana Pendidikan, 2024)
In this study, it focuses on analyzing the influence of product quality factors, price factors, place factors and promotional factors on product purchasing decisions at Mahalona Coffee shop, Karawang. Quantitative methods were used in this study and used descriptive and verification approaches. Primary data in this study is in the form of a questionnaire with purposive sampling technique in collecting research data. The population in this study were consumers of Mahalona coffee shop, Karawang, whose number could not be known with certainty because the visitor population could not be counted and the list of names of population members was unknown, which was then processed using the Lemeshow formula to determine the sample of 100. The results of this study were assisted using SPSS version 26 and Microsoft Excel 2019. This study provides the fact that product quality factors (X1) and promotional factors (X4) have a significant effect on purchasing decisions (Y), while price factors (X2) and place factors (X3) have an effect but are not significant to purchasing decisions (Y). Meanwhile, the test results on all variables are simultaneously said to have a significant effect on purchasing decisions. And overall the results of R square produce a value of 70.4%.